PERAN SEMANTIS VERBA BAHASA TETUN DI TIMOR LESTE - Antonius Maturbongs (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Tetun is one of the moderate category languages in number of speakers in Timor Leste.This research explains and describes verbal semantic roles of Tetun language, i.e.verbal semantic roles of state bs, action, and process. Data analysis uses qualitativedescriptive method. The result indicates that verbal semantic roles of state in Tetunlanguage tends to show state of physical, state of mind. Verbal semantic roles of actionis a representation of natural meanings of act, happen, and displacement/movement.Verbal semantic roles of process in Tetun language has both regularity of movementand event. Verbal semantic roles of state, action, and process show interestingimplication, i.e. the existence of correlation between the inherently valence of state,action, and process verbs, especially on the first exponent.